The Source and Significance of Coincidences: A Hard Look at the Astonishing Evidence by Sharon Hewitt Rawlette - Storm, Lance (Journal of Scientific Exploration, 2020)
Sharon Rawlette’s offering to those appreciative (even enamoured) of the fickle, unpredictable, and mystifying world of coincidences, is a mammoth tome of 600+ pages ambitiously bearing the title The Source and Significance of Coincidences. As the title suggests, Rawlette seeks to explain who or what might cause coincidences (these explanations are far-ranging), and she endeavours to point out what they mean (usually they only have a positive spin). Right from the outset, Rawlette gives the term coincidence its own special definition, but anyone steeped in the Jungian tradition cannot help but see that Rawlette’s brand of coincidence runs parallel with Jung’s (1952/1969) meaningful coincidence, better known as synchronicity. The many examples she gives fit the bill, and they don’t require an overly flexible turn of mind to see it, but Rawlette insists on distinguishing her type of coincidences from paranormal experiences (‘telepathic messages’), after-death (discarnate) communications, and even Jung’s synchronicity. It is unfortunate that her definitions do not shore up the distinction she wishes to make: coincidences are “physical events that appear to reflect the contents of people’s minds”, and they convey “personal meaning” (p. 11)—but that’s synchronicity! Rawlette also includes as coincidences those events “without any obviously profound meaning and yet seem too improbable to be the mere products of chance” (p. 11). That could still be synchronicity—one couldn’t spot a coincidence if it didn’t have some meaning (Flew, 1953), which may not dawn on someone as being profound until some time has passed.